KINERJA CAMPURAN SPLIT MASTIC ASPHALT (SMA) YANG MENGGUNAKAN SERAT SELULOSA ALAMI DEDAK PADI - Tahir, Anas (Jurnal REKAYASA dan MANAJEMEN TRANSPORTASI, 2011)
Split Mastic Asphalt (SMA) is one of the hot mix asphalt concretes use with open graded and it has high coarse agregate content (70% - 80%) and a high asphalt content. Since the content of the high asphalt needs requires additional material such as cellulosa fiber to stabilize the asphalt. Through with this study, the another try to use rice bran as the additional material. In addition, rice bran is a natural cellulose fiber which cames from the rice milling proces. It was relatifevely cheaper than the cellulose fibers synthesis.The results showed that the use of rice bran affects the characteristics of the mixture Split Mastics Asphalt (SMA). The stability of the mixture by using cellulose (rice bran) as an additive in a mixture of Split Mastics Asphalt (SMA) generally meet the specifications, except the asphalt content of 7.5% - 8% with rice bran content of 8% - 9%.Value of Flexibility in the mixture showed a tendency to decrease. On the asphalt content of 5.5% shows the highest flexibility and does not meet specifications unless the content of rice bran 8% - 9%. that gives a good mix of performance on asphalt content. The value of flexibility that gives a good mix of performance on asphalt content of 6.5% - 7.5% with bran content of 6% - 8%.